(untitled) (Journal of Computational Mathematics, 2018)
This paper deals with the discontinuous Galerkin (DG) methods for delay differential equations. By an orthogonal analysis in each element, the superconvergence results of the methods are derived at nodal points and eigenpoints. Numerical experiments will be carried our to verify the effectiveness and the theoretical results of the proposed methods.